Effect of Boiling Time on the Quality of Tomato Sauce - PHIMSALA , Phuangsavat; NORTOUALEE, Leulee; PHONEMANY, Chanda; LORKHAMHEUANG, Vonesy; SEELAPHON, Noknoy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is to study the optimal time for boiling tomato sauce, sensory testing, physico-chemical and microbiological quality analysis. Filter and add the mixture, then boil at 100°C by time (minutes) 4 different levels as experimental (Treatment; T) as: T10, T15, T20 and T25. From bringing the 4 treatment tomato sauce products from processing to the tactile sensory test using 50 taste testers to compare various characteristics such as: overall liking, color, appearance, sweetness, sourness, viscosity, overall odor, taste and sensation after-swallowing, It was found that the T25 received a higher acceptance score than the other treatment with a confidence level of 95% (P≤0.05) with values equal to 8.05, 8.14, 8 .10, 8.36, 8.48, 8.36, 8.42 and 8.44 respectively from a full score of 9. From the behavioral test, the testers give acceptance and decide to buy the tomato sauce product equal to 100%, which shows that there is a high acceptance value and if there is this product in the market, there will be buyers of this product. For the physical-chemical quality analysis, it was found that: the results of Viscosity (VS), ˚Brix, potential of the Hydrogen ions (pH), moisture content (%MC), drying yield (%DY) and total solid content (%TS) in the T25 were equal to 5.50 cm, 37.33, 3.19, 70.71%, 70.66% and 29.24% respectively. As for the L* and a* values, it was found that all 4 boiling periods had no statistical difference at the 95% confidence level (p≥0.05), while the b* value had a statistical difference at the 95% confidence level (p≤0.05) and from the measurement of the amount of antioxidants such as: Chlorophyll a, Chlorophyll b, Lycopene and Β-Carotene in Treatment T25 have values equal to -0.08, 0.86, 0.24 and -0.25 respectively. As for the microbiological quality analysis results after storage at refrigerator temperature for 30 days, all 4 treatments did not exceed the standard. Therefore, when considering the results of the study, the optimal boiling time is 25 minutes (T25) as a suitable tomato sauce product in this research